Barbados : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that Barbados's economy has recovered partially from the 2001-02 recession, as real GDP grew by an estimated 2 percent in 2003, led by a recovery in the tourism sector. Inflation remained low at 1.5 percent, reflecting the currency peg. The external current account deficit widened in 2003, as merchandise exports declined and imports recovered from their low recession levels. Broad money growth decelerated in 2003, although it was still faster than GDP growth, and banks became increasingly liquid.